Discovery of brevijanazines from Aspergillus brevijanus reveals the molecular basis for p-nitrobenzoic acid in fungi. Issue 43 (10th May 2022) - Li, Hang; Mirzayans, Paul M.; Butler, Mark S.; Lacey, Alastair E.; Vuong, Daniel; Chen, Rachel; Kalaitzis, John A.; Moggach, Stephen A.; Lacey, Ernest; Piggott, Andrew M.; Chooi, Yit-Heng
Abstract : The discovery of a novel family of p -nitrobenzoylated piperazines from Aspergillus brevijanus revealed that the biosynthesis of p -nitrobenzoic acid in fungi is catalysed by a PABA synthase, an aminodeoxychorismate synthase and a cytochrome P450. Abstract : The brevijanazines are novel p -nitrobenzoylated piperazines isolated from Aspergillus brevijanus . Their structures were elucidated by spectroscopic analysis, X-ray crystallography and total synthesis. Heterologous biosynthesis, precursor feeding and in vitro microsomal assays unveiled the biosynthetic pathway to the brevijanazines, featuring a cytochrome P450 oxygenase that converts p -aminobenzoic acid to p -nitrobenzoic acid.